A new species of Cossidophaga Baranov from Indonesia (Diptera: Tachinidae), a parasitoid of the carpenter moth, Polyphagozerra coffeae (Nietner) (Lepidoptera: Cossidae). (1st October 2020) - Tachi, Takuji; Shima, Hiroshi; de Souza Tavares, Wagner; Tarigan, Marthin
ABSTRACT: The carpenter moth Polyphagozerra coffeae (Nietner) (Lepidoptera: Cossidae) is an important pest of commercial plantations of Eucalyptus pellita F. Muell. and the hybrid E. pellita × Eucalyptus grandis W. Hill. ex Maiden (Myrtaceae) in Riau, Indonesia. This study describes a new species of tachinid fly, Cossidophaga coffeae sp. nov ., record its host, P. coffeae, and redescribe the type species of C. atkinsoni (Aubertin). urn:lsid:zoobank.org:pub:13CC511E-9B01-4E44-9BAD-98FAA92DC205